Is It Speech or Song? Effect of Melody Priming on Pitch Perception of Modified Mandarin Speech - Chen-Gia Tsai; Chia-Wei Li (Brain Sciences, 2019)
Tonal languages make use of pitch variation for distinguishing lexical semantics, and their melodic richness seems comparable to that of music. The present study investigated a novel priming effect of melody on the pitch processing of Mandarin speech. When a spoken Mandarin utterance is preceded by a musical melody, which mimics the melody of the utterance, the listener is likely to perceive this utterance as song. We used functional magnetic resonance imaging to examine the neural substrates of this speech-to-song transformation. Pitch contours of spoken utterances were modified so that these utterances can be perceived as either speech or song. When modified speech (target) was preceded by a musical melody (prime) that mimics the speech melody, a task of judging the melodic similarity between the target and prime was associated with increased activity in the inferior frontal gyrus (IFG) and superior/middle temporal gyrus (STG/MTG) during target perception. We suggest that the pars triangularis of the right IFG may allocate attentional resources to the multi-modal processing of speech melody, and the STG/MTG may integrate the phonological and musical (melodic) information of this stimulus. These results are discussed in relation to subvocal rehearsal, a speech-to-song illusion, and song perception.